Vocational Education-Based Acquisition of Skills to Curb Youth Restiveness: The Internet of Skills Approach - Ecoma, Chinyere S; Iheoma, Nweke Pearl; Ngang, Ngang Bassey (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
Lack of pertinent skills has been linked to youth unrest brought on by rising unemployment rates. This work offered a method for students to learn without the assistance of a subject-matter expert (SME). The paper is a source of information that focuses on using the internet to develop entrepreneurial skills to address the issue of youth unemployment in developing countries. It is a fact that entrepreneurial skills are essential to job creation; active use of the internet to acquire pertinent knowledge could lead to self-actualization. Youth unemployment in developing nations is on the rise. This paper used real-world examples to demonstrate how internet resources can be helpful for performing tasks both at home and in the workplace. For example, studying saponification in chemistry can be taught similarly to how it is used in the soap manufacturing industry. Information on troubleshooting guides for electrical machines (electric motors and synchronous generators) was also provided from secondary sources. Finally, the